Quizizz Paper Mode Increases Student Learning Motivation in Mathematics Lessons at SD Plus Darul Ilmi Murni - Hasibuan, Mara Purba (Yana Research, 2023)
Mathematics is a very useful subject in everyday life. However, mathematics is seen as the most difficult subject for students, especially students in elementary schools. Therefore, a teacher needs learning media that can be fun and motivate students in learning mathematics, one of which is Quizizz paper mode. Quizizz paper mode is used as a learning media in class so that mathematics learning is more interactive and fun for students. This study aims to find out whether the paper mode quizizz can improve students' understanding of number names and number symbols. Classroom action research is used in this study and 2 cycles are carried out in class 1 SD Darul Ilmi Medan. In cycle I, the average score is 78. In cycle II, the increase in students' knowledge in learning number names experienced a better increase than the previous cycle (cycle I). The average score obtained by students is 95. It shows that the use of paper mode quiziz can increase students' understanding of understanding the names and symbol of numbers in mathematics. Besides that, students are also interested and motivated in the learning process using paper mode quizizz.